Iron man: extremis ebook Extremis - special. - Ellis, Warren (Iron Man (2005)., 2011)
Collects IRON MAN (2004) #1-6. A landscape of terrifying new technologies threatens to overwhelm fragile mankind! What is Extremis, who has unleashed it, and what does its emergence portend for the world?